2021
DOI: 10.3390/ph14030279
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Evidence for the Choice of the Direct Oral Anticoagulant in Patients with Atrial Fibrillation According to Creatinine Clearance

Abstract: Atrial fibrillation (AF) often coexists with chronic kidney disease (CKD), which confer to the patient a higher risk of both thromboembolic and hemorrhagic events. Oral anticoagulation therapy, nowadays preferably with direct oral anticoagulants (DOACs), represents the cornerstone for ischemic stroke prevention in high-risk patients. However, all four available DOACs (dabigatran, apixaban, rivaroxaban and edoxaban) are eliminated by the kidneys to some extent. Reduced kidney function facilitates DOACs accumula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(18 citation statements)
references
References 53 publications
0
7
0
Order By: Relevance
“…A prudent approach is to check renal function at the initiation of treatment with NOACs, after 3 months and then every year, except for high-risk patients (the elderly >75 years, patients with low body mass) who require monitoring at least every 6 months 26. In patients with declining renal function, the current position of EHRA is to estimate the recheck intervals individually using a simple calculation: if CrCl is ≤60 mL/min, the recheck interval in months is CrCl/10 11…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A prudent approach is to check renal function at the initiation of treatment with NOACs, after 3 months and then every year, except for high-risk patients (the elderly >75 years, patients with low body mass) who require monitoring at least every 6 months 26. In patients with declining renal function, the current position of EHRA is to estimate the recheck intervals individually using a simple calculation: if CrCl is ≤60 mL/min, the recheck interval in months is CrCl/10 11…”
Section: Discussionmentioning
confidence: 99%
“…This is particularly relevant since the kidneys are responsible for partially eliminating all four available NOACs. Dabigatran has the greatest extent of renal elimination (80%), while 50%, 35% and 27% of edoxaban, rivaroxaban and apixaban, respectively, are cleared via the kidneys 11…”
Section: Introductionmentioning
confidence: 99%
“…Although the phase III trials excluded patients with severe renal impairment of a creatinine clearance (CrCl) < 25 to 30 mL/min, some cohort studies have demonstrated that NOACs also provide effective thromboprophylaxis in AF patients with mild to moderate renal dysfunction (CrCl of 30-79 mL/min) [44]. Adopted from [29,[38][39][40]45]. Legend: QD-once a day; BID-twice a day; P-gP-P glycoprotein transporter involved in absorption and renal clearance-plasma levels may be influenced by P-gP inducers or inhibitors; CYP450-cytochrome P 450 CYP3A4 involved in hepatic clearance-plasma levels may be affected by CYP3A4 inducers or inhibitors; Cmax-peak concentration; t1/2-half-life; INR-international normalized ratio.…”
Section: Oral Anticoagulation In Patients With Atrial Fibrillation-what Does Available Evidence Tell Us?mentioning
confidence: 99%
“…Thus, assessment of the individual patient risks and regular monitoring of renal function is crucial to guide dose adjustments of NOACs [ 51 ]. It is important to note, that none of the NOACs have been approved in Europe for patients with CrCl < 15 mL/min or on dialysis [ 45 ].…”
Section: Current International Guidelines For Oral Anticoagulation Treatment In Ckdmentioning
confidence: 99%
See 1 more Smart Citation